Musculoskeletal Injuries Associated with Yoga Practice - a Literature Review - Magda Niemaszyk; Aleksandra Truszczyńska-Baszak (Rehabilitacja Medyczna)
Introduction: Yoga is a popular form of physical activity used by healthy people and patients with various ailments. There is evidence of both positive and negative effects of practicing yoga on both physical and psychological aspects. There is a lack of extensive knowledge about the factors that increase the risk of injury in yoga practitioners.Objectives: The aim of the study was to determine the occurrence and characteristics of motor organ overload associated with practicing yoga among people undertaking this form of physical activity on the basis of a literature review, including answering the following questions: 1. What are the health benefits of practicing yoga?; 2. What are the risk factors for an injury in the yoga training?Material and methods: The current professional literature was analysed based on a review of Internet databases from last 10 years, including Pubmed. The yoga, injury, adverse events, musculoskeletal system, physiotherapy keywords were used.Results: From the abovementioned Internet databases, 32 items of the current professional literature on the analysed variables were identified, 8 articles were included in the analysis of the beneficial effects of yoga and 7 articles were comprised on the detailed list of musculoskeletal overloads.Conclusions: The benefits of practicing yoga include pain reduction, increasing range of motion in the joints, improving the performance of daily activities and the quality of life in physical and mental spheres. The risk factors of experiencing the injury mentioned in the literature concerned old age, yoga practice, and the presence of chronic diseases.